Theography: Subject, theology, and praxis in geographies of religion. (June 2017) - Sutherland, Callum
This paper intervenes in the recent movement in religious geographies to produce more nuanced understandings of the religious subject. By introducing the concept of theography, this paper explores a religious reflexivity that directs subjects towards struggles over the content of theology, its effects on their spatial imagination, and their praxis. Theography advances conversations about praxis in the geography of religion by tying together poststructural scholarship regarding the religious subject's potential to subvert abstract categorization, geographies concerning the subject's reframing of theology, and philosophical contributions vis-à-vis praxes that stem from particular understandings of transcendence.